Vitamin D status among long-term survivors of testicular cancer - Schepisi, Giuseppe (Oncotarget, 2016)
A correlation between disturbances in hormone levels and the onset of metabolic disorders has been reported in long-term survivors of testicular cancer (TC). We evaluated serum vitamin D levels and other biological parameters in a consecutive series of 61 long-term (≥3 years) unilateral TC survivors with a median a follow-up of 4 years and in a cohort of healthy males. Deficient vitamin D levels were observed in 10 (17%) of the 58 long-term unilateral TC survivors but were not reported in healthy males (p=.019, Fisher test). Median vitamin D levels were 18.6 ug/L in 58 assessable TC survivors and 23.6 ug/L in 40 healthy males (p=.031). In univariate logistic regression analysis, TC diagnosis was associated with inadequate levels of vitamin D (p=.047). Vitamin D levels were lower when follow-up was > 10 years, albeit this difference was not statistically significant (p=.074). Long-term (especially > 10 years) TC survivors may have difficulty maintaining optimal vitamin D levels. Larger studies are needed to better characterize vitamin D status and possible correlations with premature hormonal aging reported in long-term TC survivors.